Microevolution, speciation and macroevolution in rhizobia: Genomic mechanisms and selective patterns - Provorov, Nikolay A.; Andronov, Evgeny E.; Kimeklis, Anastasiia K.; Onishchuk, Olga P.; Igolkina, Anna A.; Karasev, Evgeny S. (Frontiers in Plant Science, 2022)
Nodule bacteria (rhizobia), N2-fixing symbionts of leguminous plants represent an excellent model to study the fundamental issues of evolutionary biology including the tradeoff between microevolution, speciation and macroevolution which remains poorly understood for free-living organisms. Taxonomically, rhizobia are extremely diverse: they are represented by nearly a dozen families of α-proteobacteria (Rhizobiales) and by some β-proteobacteria. Their genomes are composed of core parts including the house-keeping genes (hkg) and of accessory parts including symbiotically specialized (sym) genes. In multipartite genomes of evolutionary advanced fast-growing species (Rhizobiaceae), sym genes are clustered on extra-chromosomal replicons (megaplasmids, chromids) facilitating the gene transfer in plant-associated microbial communities. In this review, we demonstrate that in rhizobia, microevolution and speciation involve different genomic and ecological mechanisms: the first one is based on the diversification of sym genes occurring under the impacts of host-induced natural selection (including its disruptive, frequency-dependent and group forms), the second one – on the diversification of hkgs under the impacts of host-independent, presumably edaphic factors. By contrast, macroevolution represents the polyphyletic origin of super-species taxa which is dependent on the transfer of sym genes from rhizobia to various soil-born bacteria. Since the expression of newly acquired sym genes on the foreign genomic backgrounds is usually restricted, conversion of resulted recombinants into the novel rhizobia species involves the post-transfer genetic changes. They are presumably supported by the host-induced selective processes resulting in sequential derepression of nod genes responsible for nodulation, and of nif/fix genes responsible for symbiotic N2 fixation.